Genome-wide identification and comprehensive analysis of EuFLS genes in Eucommia ulmoides reveals their roles in growth, development, and abiotic stress response - Liu, Jun; Cheng, Tingting; Wang, Lili; Lian, Conglong; Ma, Rui; Feng, Weimeng; Lan, Jinxun; Zhang, Bao; Du, Qingxin; Kou, Jiefeng; Chen, Suiqing (Frontiers in Plant Science, 2025)
Flavonoids with great medicinal value play an important role in plant individual growth and stress resistance. Flavonol synthase (FLS) is one of the key enzymes to synthesize flavonoids. However, there is no information available about FLS family in Eucommia ulmoides, an ancient and precious plant with great economic value. In this study, twelve EuFLS genes were identified and classified into two distinct subgroups based on their phylogenetic trees, these genes were unevenly distributed across eight chromosomes. Gene structure analysis revealed that EuFLS genes contained between two and four introns. The number of introns within members of the same evolutionary branch was generally consistent. The EuFLS promoters region contained a substantial number of hormone-responsive, stress-responsive, and light-responsive. RNA-seq data revealed tissue-specific expression patterns, EuFLS2 and EuFLS9 displayed the highest expression levels in leaves, whereas EuFLS4 the peak expression level in the xylem. The majority of EuFLS genes showed higher expression levels in red leaves and male flowers; furthermore, these genes contributed to leaf development and rubber biosynthesis. qRT-PCR analysis showed that most EuFLS genes downregulation under ABA and SA treatments. EuFLSs displayed divergent expression trends under MeJA treatment. While drought stress significantly induced the expression of most EuFLSs, especially, EuFLS9 was induced 50-fold at 3 h, suggesting that FLS genes in E. ulmoides regulate plant growth and respond to different stresses by following different hormone signaling pathways, which laid a valuable foundation for further understanding the function of FLS genes in multiple stress responses and phytohormone crosstalk in E. ulmoides.